2019
DOI: 10.1016/j.chembiol.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

C-Nucleoside Formation in the Biosynthesis of the Antifungal Malayamycin A

Abstract: Highlights d The gene cluster for the antifungal C-nucleoside malayamycin A has been identified d 5 0 -Pseudouridine monophosphate (5 0 -J-MP) is an essential precursor d 3 0 -Enoylpyruvyltransferase MalO specifically acts on 5 0 -J-MP, not UMP d An engineered strain produces the non-natural N-linked analog of malayamycin A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Accordingly, it is possible that indigoidine biosynthesis from an increasing number of potential pathways may be associated with related unknown C- nucleoside molecules, because analogs of the MinA-MinB pair are in several cases concomitantly present in the specific gene clusters (Figure S5). L-glutamate is the common precursor for the aglycon of the C- nucleoside antibiotics, including MIN, formycin, pyrazofurin, and showdomycin (Suhadolnik and Reichenbach, 1981), which until recently have been unexplored at the molecular level (Hong et al., 2019, Palmu et al., 2017, Sosio et al., 2018, Wang et al., 2019). Hence, we propose that further insight into the molecular logics underlying the biosynthesis of C- nucleoside antibiotics will identify diverse and unique enzymes for potential synthetic biology purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is possible that indigoidine biosynthesis from an increasing number of potential pathways may be associated with related unknown C- nucleoside molecules, because analogs of the MinA-MinB pair are in several cases concomitantly present in the specific gene clusters (Figure S5). L-glutamate is the common precursor for the aglycon of the C- nucleoside antibiotics, including MIN, formycin, pyrazofurin, and showdomycin (Suhadolnik and Reichenbach, 1981), which until recently have been unexplored at the molecular level (Hong et al., 2019, Palmu et al., 2017, Sosio et al., 2018, Wang et al., 2019). Hence, we propose that further insight into the molecular logics underlying the biosynthesis of C- nucleoside antibiotics will identify diverse and unique enzymes for potential synthetic biology purposes.…”
Section: Resultsmentioning
confidence: 99%
“…The C -nucleoside antibiotics (Figure 1) constitute an important sub-group of microbial natural products with unusual structural features and diverse biological activities (Isono, 1988, Maffioli et al., 2017). Their biosynthesis generally follows a succinct logic, with sequential modifications of simple precursors originating from primary metabolism (Hong et al., 2019, Isono, 1988, Palmu et al., 2017, Sosio et al., 2018, Wang et al., 2019). Less typically, minimycin (MIN, also called oxazinomycin) is produced by diverse bacterial strains, either Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nature has developed several diverse strategies for C-glycosidic bond construction during the biosynthesis of this group of antibiotics. Showdomycin biosynthesis uses a YeiN-like C-glycosyltransferase to build the C-C bond (3), while the biosynthesis of pseudouridimycin and malayamycin exploits a tRNA pseudouridylate synthase (TruD-like) for C-glycosidic bond construction (4,26). In the present study, FOR-A and PRF-A are shown to harness a totally different ␤-RFA-P synthase-like enzyme (ForT/PrfT) to catalyze the formation of C-glycosides (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Actually, nature has developed diverse strategies for C -glycosidic bond construction during the biosynthesis of this group of antibiotics. Showdomycin biosynthesis uses a YeiN-like C -glycosyltransferase to build the C-C bond (5), while pseudouridimycin and malayamycin are deduced to exploit a tRNA (TruD-like) pseudouridylate synthase for C -glycosidic bond construction (6, 28). In the present study, FOR-A and PRF-A harness a totally different β-RFA-P synthase-like enzyme (ForT/PrfE) to catalyze the formation of C -glycosides.…”
Section: Discussionmentioning
confidence: 99%